Temperature effects on the phase behaviour of PSBMA polymer - Lim, Kai Loon (Nanyang Technological University, 2021)
Poly(sulfobetaine methacrylate) (PSBMA) polymers is a promising material in biomedical and drug development due to their high hydrophilicity, good anti-biofouling property, anti-polyelectrolyte, and biocompatibility. It is a class of zwitterionic polymer with sulfobetaine and amine function groups giving it strong hydrophilic properties. Due to this property, it is widely used as a copolymer by grafting PSBMA onto other materials. However, the phase behaviour of PSBMA is not well established. Thus, the project analyses PSBMA polymer to determine its phase behaviour and develop a phase diagram of PSBMA polymer. The polymer is analysed experimentally by turbidity method via UV-Vis spectrometry. The phase transition temperature is determined from the spectra and plotted against a range of polymer concentration to determine the phase diagram. Results from the phase diagram show that the PSBMA sample display a single-phase closed loop of a mixture of both Upper Critical Solution Temperature (UCST) and Lower Critical Solution Temperature (LCST) behaviour. Besides, the UCST and LCST showed a trend of decreasing transition temperature as polymer concentration increase.